2016
DOI: 10.12659/msm.899023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture on Interstitial Cells of Cajal (ICC) Ultrastructure and Connexin 43 Protein Expression in the Gastrointestinal Tract of Functional Dyspepsia (FD) Rats

Abstract: BackgroundGastrointestinal motility disorder is the main clinical manifestation in functional dyspepsia (FD) patients. Electroacupuncture is effective in improving gastrointestinal motility disorder in FD; however, the underlying mechanism remains unclear. It has been demonstrated that interstitial cells of Cajal (ICC) are pacemaker cells in the gastrointestinal tract, and the pacemaker potential is transmitted to nearby cells through gap junctions between ICC or ICC and the smooth muscle. Therefore, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In this study, to obtain more stable FD model, the tails of rats were pinched twice a day for 4 weeks. Our results showed that the rats in model group showed a significant decrease in food intake, abnormal excreta, slower weight gain, delayed gastric emptying, and no remarkable pathological changes in the gastric antrum tissue, which was consistent with the previous study . The results suggest that FD model was successfully induced by chronic stress via tail clamping.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, to obtain more stable FD model, the tails of rats were pinched twice a day for 4 weeks. Our results showed that the rats in model group showed a significant decrease in food intake, abnormal excreta, slower weight gain, delayed gastric emptying, and no remarkable pathological changes in the gastric antrum tissue, which was consistent with the previous study . The results suggest that FD model was successfully induced by chronic stress via tail clamping.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the course of FD is always chronic with recurrent features. At the previous studies, FD model in rats was generally induced by acute physical stress—that is, the tails of rats were pinched four times once a day for 1 week . In this study, to obtain more stable FD model, the tails of rats were pinched twice a day for 4 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…For example, electroacupuncture was recently shown to effectively alleviate ICC damage and reduce recombinant connexin 43 levels, thus improving gastrointestinal motility disorders. 17 Gastrointestinal ICCs express the surface receptor c‐kit, which is widely used to specifically detect ICCs, thereby serving as an indicator of the degree of gastrointestinal motility. 18 , 19 Thus, in this study we investigated the potential relationship between the severity of trauma and expression of c‐kit protein in ICCs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their fundamental role in the gastrointestinal tract, ICCs may be an important target for gastrointestinal motility therapies. For example, electroacupuncture was recently shown to effectively alleviate ICC damage and reduce recombinant connexin 43 levels, thus improving gastrointestinal motility disorders 17 . Gastrointestinal ICCs express the surface receptor c‐kit, which is widely used to specifically detect ICCs, thereby serving as an indicator of the degree of gastrointestinal motility 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…ICC is the pacemaker of gastrointestinal motility, which stimulates the rhythmic peristalsis of the gastrointestinal tract by spontaneously generated electrical slow waves. Therefore, structural and functional abnormalities of ICC are closely related to gastrointestinal motility disorders and the cause of many gastrointestinal diseases (Sanders et al, 2014;Zhang et al, 2016). FD is a representative disease of gastrointestinal motility disorder.…”
Section: Introductionmentioning
confidence: 99%